Building a Gender-Responsive Higher Education Institution through Collaborative Governance - Fithriyyah, Mustiqowati Ummul; Sari, Ilmi Puspita; Monalisa, Monalisa (An-Nida', 2024)
This research aims to determine the extent of the implementation of Gender Responsive Higher Education (PTRG) at the State Islamic University Sultan Syarif Kasim Riau (UIN Suska Riau) using the collaborative governance model by Ansel and Gash. Collaborative governance is a part that supports the implementation of gender-responsive indicators in higher education. It examines the commitment and trust built by stakeholders in addressing gender disparities. The methodology used in this research is descriptive qualitative, with data obtained from observations in various faculties of UIN Suska Riau and interviews with 23 informants consisting of 19 academic members, 1 private sector representative, 2 Non-Government Organization (NGO) members, and 1 community member. The findings show that the implementation of Gender Responsive Higher Education at UIN Suska Riau is carried out by various actors in line with collaborative governance actors, including the government, private sector, and community. In this research, the campus community acts as the government actor on behalf of the university institution, PT. Orbit Ventura Indonesia as the private sector actor, Rumah KitaB and AMAN as NGOs, and the community has been optimal. This is evident from most of the gender-responsive higher education indicators is well achieved. Stakeholder collaboration leads to actions that strengthen planning in the implementation of gender responsiveness.Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana pelaksanaan Perguruan Tinggi Responsive Gender (PTRG) di Universitas Islam Negeri Sultan Syarif Kasim Riau (UIN Suska Riau) dengan menggunakan teori tata kelola kolaboratif model Ansel dan Gash. Tata kelola kolaboratif menjadi bagian yang mendukung pelaksanaan indikator responsif gender Perguruan Tinggi. Melihat komitmen dan kepercayaan yang dibangun oleh para pemangku kepentingan dalam menyelesaikan ketimpangan gender. Metodologi yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan perolehan data dari observasi ke berbagai fakultas UIN Suska Riau dan wawancara dengan 23 informan yang terdiri dari sivitas akademika sebanyak 19 orang, sektor swasta 1 orang, anggota Lembaga Swadaya Masyarakat (LSM) 2 orang dan masyarakat 1 orang. Temuan penelitian menunjukkan bahwasanya pelaksanaan Perguruan Tinggi Responsive Gender di UIN Suska Riau dilakukan oleh berbagai aktor sesuai dengan aktor tata kelola kolaboratif yang terdiri dari pemerintah, sektor swasta dan masyarakat maka aktor dalam penelitian ini warga kampus sebagai aktor pemerintah atas nama instansi perguruan tinggi, PT. Orbit Ventura Indonesia sebagai aktor swasta, Rumah KitaB dan AMAN sebagai LSM serta masyarakat dalam pelaksanaannya sudah optimal. Hal ini terlihat dari sebagaian besar indikator Perguruan Tinggi Responsive Gender yang tercapai dengan baik. Kolaborasi pemangku kepentingan menimbulkan tindakan yang mengarah pada penguatan perencanaan dalam pelaksanaan responsif gender.